2006
DOI: 10.1091/mbc.e05-08-0794
|View full text |Cite
|
Sign up to set email alerts
|

KEL-8 Is a Substrate Receptor for CUL3-dependent Ubiquitin Ligase That Regulates Synaptic Glutamate Receptor Turnover

Abstract: The regulated localization of ␣-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA)-type glutamate receptors (AMPARs) to synapses is an important component of synaptic signaling and plasticity. Regulated ubiquitination and endocytosis determine the synaptic levels of AMPARs, but it is unclear which factors conduct these processes. To identify genes that regulate AMPAR synaptic abundance, we screened for mutants that accumulate high synaptic levels of the AMPAR subunit GLR-1 in Caenorhabditis elegans. GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 65 publications
1
77
0
Order By: Relevance
“…If mutations in rab-10 or lin-10 result in the accumulation of GLR-1 at an internal membrane trafficking compartment, then these mutations should result in corresponding GLR-1-mediated behavioral phenotypes (Burbea et al, 2002;Juo and Kaplan, 2004;Shim et al, 2004;Umemura et al, 2005;Schaefer and Rongo, 2006). In C. elegans, GLR-1 signaling positively regulates spontaneous reversals during forward locomotion as animals forage for food (Mellem et al, 2002;Zheng et al, 2004).…”
Section: Mutations In Either Rab-10 or Lin-10 Results In Behavioral Phmentioning
confidence: 99%
See 2 more Smart Citations
“…If mutations in rab-10 or lin-10 result in the accumulation of GLR-1 at an internal membrane trafficking compartment, then these mutations should result in corresponding GLR-1-mediated behavioral phenotypes (Burbea et al, 2002;Juo and Kaplan, 2004;Shim et al, 2004;Umemura et al, 2005;Schaefer and Rongo, 2006). In C. elegans, GLR-1 signaling positively regulates spontaneous reversals during forward locomotion as animals forage for food (Mellem et al, 2002;Zheng et al, 2004).…”
Section: Mutations In Either Rab-10 or Lin-10 Results In Behavioral Phmentioning
confidence: 99%
“…18, November 2007 4389 (White et al, 1986;Kaplan and Horvitz, 1993). Mutants with reduced GLR-1 activity have a lower frequency of spontaneous reversals and are nose-touch insensitive, whereas mutants with increased GLR-1 activity (e.g., higher levels of synaptic GLR-1 at the cell surface) have a higher frequency of spontaneous reversals (Hart et al, 1995;Maricq et al, 1995;Burbea et al, 2002;Mellem et al, 2002;Juo and Kaplan, 2004;Shim et al, 2004;Zheng et al, 2004;Umemura et al, 2005;Schaefer and Rongo, 2006). We examined GLR-1-mediated behaviors in wild-type animals and in animals with mutations in lin-10 and rab-10.…”
Section: Rab-10 Regulates Glur Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Schaefer and Rongo (71) reported that KEL-8 is involved in the degradation of glutamate receptors in neurons. However, KEL-8 did not directly interact with the glutamate receptors as the substrate adaptor.…”
Section: Discussionmentioning
confidence: 99%
“…The UPS has been shown to regulate GluR synaptic abundance both directly and indirectly. In C. elegans, direct ubiquitination and proteasomal degradation of GluR1 subunits has been demonstrated (Burbea et al, 2002), but the UPS also indirectly regulates GluR1 synaptic abundance through multiple other pathways (Juo and Kaplan, 2004;Dreier et al, 2005;Schaefer and Rongo, 2006). In cultured rat hippocampal neurons, indirect regulation of AMPA receptors has been demonstrated through ubiquitination and degradation of the postsynaptic scaffolding protein PSD-95 (Colledge et al, 2003), and agonist-induced AMPA receptor internalization has been shown to be dependent on UPSmediated degradation of an undetermined synaptic protein (Patrick et al, 2003).…”
Section: Introductionmentioning
confidence: 99%